The Diversity of Indigenous Medicine of Sri Lanka: A Cross Sectional Study - Samarakoon, S.M.S.; Rathnayake, A.; Herapathdeniya, S.K.M.K. (Faculty of Indigenous Medicine, University of Colombo, 2021)
Traditional Medical System in Sri Lanka comprises Ayurveda, Siddha, Unani, and Deshiya Chikitsa. Deshiya Chikitsa is a purely native kind of medicine that has been practicing since pre-historic period of Sri Lanka. The general objective of this study was to investigate diversity of indigenous medicine (IM) in the Moneragala District. Ninety registered physicians were selected from the population using purposive sampling method. Qualitative data collection methods were used for collecting primary data. The Moneragala District has rich diversity of IM and eighteen medical genealogies and 325 indigenous physicians were identified. The majority of physicians are unregistered with the Ayurvedic Medical Council. Sarpavisha wedakama and Kadumbindum wedakama are the wide spread branches that prevail in the Moneragala District. The other identified branches are demonology (Bhutavidya), treatment for stray-dog bite (Jalabhitika), abscess and sore (Gedivana), common ailments (Sarvanga), eye-diseases (Akshiroga), psychiatric disorders (Manasaroga) and skin diseases (Charmaroga).
Keywords: Diversity; Medical Genealogies; Indigenous Medicine; Deshiya Chikitsa